2017
DOI: 10.1111/coa.12914
|View full text |Cite
|
Sign up to set email alerts
|

Do laryngoscopic findings reflect the characteristics of reflux in patients with laryngopharyngeal reflux?

Abstract: Objective: To analyse the association between 24-hour multichannel intraluminal impedance-pH (24-h MII-pH) parameters and each item of the reflux finding score (RFS) to determine whether the laryngoscopic findings of the RFS could reflect the characteristics of reflux in patients with laryngopharyngeal reflux (LPR).Study Design: Prospective cohort study.Settings: Tertiary care referral medical centre.Participants: Patients complaining of LPR symptoms were evaluated via a 24-hour MII-pH. Among them, 99 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Several findings, such as vocal fold erythema, leukoplakia, posterior pharyngeal wall inflammation, anterior pillar inflammation and coated tongue, are not included in the reflux finding score (RFS) and they were considered to be LPR-associated findings only to a certain extent (by about 10% to 60% of respondents). However, the findings associated with LPR may vary according to the type of reflux and patients' symptoms [26,27]. In addition, the physician's judgment is strongly influenced by his or her knowledge of the patient's complaint, which may help explain the low inter-rater reliability of the RFS [1].…”
Section: Discussionmentioning
confidence: 99%
“…Several findings, such as vocal fold erythema, leukoplakia, posterior pharyngeal wall inflammation, anterior pillar inflammation and coated tongue, are not included in the reflux finding score (RFS) and they were considered to be LPR-associated findings only to a certain extent (by about 10% to 60% of respondents). However, the findings associated with LPR may vary according to the type of reflux and patients' symptoms [26,27]. In addition, the physician's judgment is strongly influenced by his or her knowledge of the patient's complaint, which may help explain the low inter-rater reliability of the RFS [1].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of impedance‐pH monitoring, an increasing number of physicians distinguish acid, non‐acid and mixed reflux; non‐acid and mixed reflux accounting for a substantial number of LPR patients . The efficacy of PPIs for LPR should be better for acid than non‐acid and mixed reflux, as PPIs do not limit refluxate mechanically but seek only to change its acid content .…”
Section: Discussionmentioning
confidence: 99%
“…The development of MII-pH led to the identification of new subtypes of LPRD, being acid, weakly acid, mixed and nonacid LPRD. In that way, three recent studies found that the majority of patients have in fact nonacid or mixed LPRD[102-104]. The pathophysiological mechanisms of nonacid and mixed LPRD are still unknown but they could involve the activity of trypsin, conjugated and non-conjugated bile salts in the mucosa of the upper aerodigestive tract[1,105].…”
Section: Discussionmentioning
confidence: 99%